Eddy properties in the Western Mediterranean Sea from satellite altimetry and a numerical simulation. Issue 6 (12th June 2016) - Escudier, Romain; Renault, Lionel; Pascual, Ananda; Brasseur, Pierre; Chelton, Dudley; Beuvier, Jonathan
Abstract: Three different eddy detection and tracking methods are applied to the outputs of a high‐resolution simulation in the Western Mediterranean Sea in order to extract mesoscale eddy characteristics. The results are compared with the same eddy statistics derived from satellite altimetry maps over the same period. Eddy radii are around 30 km in altimetry maps whereas, in the model, they are around 20 km. This is probably due to the inability of altimetry maps to resolve the smaller mesoscale in the region. About 30 eddies are detected per day in the basin with a very heterogeneous spatial distribution and relatively short lifespans (median life around 13 days). Unlike other areas of the open ocean, they do not have a preferred direction of propagation but appear to be advected by mean currents. The number of detected eddies seems to present an annual cycle when separated according to their lifespan. With the numerical simulation, we show that anticyclones extend deeper in the water column and have a more conic shape than cyclones. Key Points: New HR simulation of the WMed returns realistic EKE levels, higher than altimetry estimates Three eddy detection methods are applied to altimetry maps and the simulation outputs In the region, eddies are small (20 km), short lived (median 13 days), and frequent (30/day)